A simple disc technique for the presumptive identification of Legionella pneumophila. Issue 12 (December 1982) - Smith, MG
Abstract : A method is described for the presumptive identification of Legionella pneumophila by the formation of satellite colonies around filter paper discs impregnated with ferric pyrophosphate and L-cysteine hydrochloride on a deficient basal medium. This technique simplifies the differentiation of picked colonies of L pneumophila from other organisms in mixed cultures from environmental and contaminated clinical samples.